Strategi Pembangunan dan Pengelolaan Hutan Kota Sabak di Kelurahan Rano Kabupaten Tanjung Jabung Timur Provinsi Jambi - Pramudia Agusni; Fuad Muchlis; Marwoto Marwoto; Rts Suwairini (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
This study aims to analyze the natural resources potential of the Sabak City Forest, analyze the benefits of development and management of the Sabak City Forest for the surrounding community both Ecologically, Economically, and Socially and Culturally, and Formulate the Development and Management Strategy of the Sabak City Forest. Based on the results of research using vegetation analysis, it shows that the potential flora in the Sabak City Forest area has a high diversity value with plant species at the Tree level and Pole level having an INP of more than 15% while for the Sapling level there are 7 species that have an INP of more than 10%. and the Semai level has 5 species that have an INP of more than 10%, meanwhile the types of Fauna are potential for the development of educational and educational attractions. This study also shows that the benefits of the development and management of the Sabak City Forest from the Ecological aspect to reduce urban environmental degradation, from the Economic aspect of the Sabak City Forest can be an opportunity to improve the economy through business opportunities, work opportunities, increase craft creativity, and provide benefits in social aspects. culture as a space for social interaction, recreational facilities, and as a cultural landmark of the city. The results of the stakeholder analysis show that the amalgamation of Quadrant I (subjects) with quadrant III (Context setters) in the development and management of the Sabak City Forest can be a major force that greatly influences the development and management of the Sabak City Forest. The strategy for the development and management of the Sabak City Forest is with the support of parties who have influence and interest in the development and management of the Sabak City Forest.